(untitled) - Chandler, Robert F. (Laguna, Philippines, 1982)
The book tells the story of a truly remarkable international agricultural research center. The impact of IRRI through rice research and the benefits it has brought to rice farmers and mankind throughout the developing world is immeasurable. It goes beyond rice. It extends to a growing family of international research centers.
Keywords: International Rice Research Institute; History